Project-Based Learning Training and Assistance for Prospective High School Teacher - Zahroh, Umy; Darmayanti, Rani; C, Choirudin; Soebagyo, Raden Imam; Nalarsih, Retno Tri (CV. BImbingan Belajar Assyfa, 2023)
Before the COVID-19 pandemic, educators were tasked with scouting out fresh approaches to teaching math. In addition, today's classrooms call for an emphasis on student-centered instruction that fosters the kinds of 21st-century talents that employers need. Abilities like critical thinking, problem-solving, teamwork, and communication are not yet optimally implemented in the new normal or post-pandemic age. This is the case because students' study habits could not be optimized as they transitioned from online and only at-home study to full-fledged schoolwork. Even in a distance learning setting, however, it is expected that these skills will continue to be developed and refined. Teachers can implement methods like project-based learning to help pupils acquire these abilities. This volunteer project has as its overarching goal the enhancement of educator competence in the pursuit of creating novel and engaging curricula for the general populace in the wake of the COVID-19 epidemic. It is envisaged that teachers at partner schools will benefit from this training and mentorship activity for project-based learning to better plan and execute such activities. Mentoring, observing, and role-playing are all components of this service. The teacher's high level of engagement in this activity is indicative of her dedication to professional development. Educators believe they grow professionally as a result of their work with project-based learning. Teachers have found success in developing project-based learning plans and implementing them in mentoring activities. After this event, similar events will be held every month, and mentorship will be provided to help teachers become more proficient in both project learning design and implementation